Patient-Specific Modeling of the Cardiovascular System Technology-Driven Personalized Medicine - Kerckhoffs, Roy C.P.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Patient-Specific Modeling of the Cardiovascular System demonstrates the design of a variety of patient-specific models within the cardiovascular system and how they could be applied on a larger scale in the clinic. Patient-specific modeling will lead to a paradigm shift within medicine if applied successfully, yet many questions need to be answered before computational modeling can be fully integrated with standard care. In order to answer the most essential questions, a selection of the world$1 (Bs leading computational modelers and clinicians have been brought together in this book. Healthcare professionals and medical students interested in the clinical application of patient-specific cardiovascular modeling will find Patient-Specific Modeling of the Cardiovascular System a valuable resource.s
Integrating State-of-the-Art Computational Modeling with Clinical Practice: The Promise of Numerical Methods -- Patient-Specific Modeling of Cardiovascular Dynamics with a Major Role for Adaptation -- Patient-Specific Modeling of Structure and Function of Cardiac Cells -- Studies of Therapeutic Strategies for Atrial Fibrillation Based on a Biophysical Model of the Human Atria -- Patient-Specific Modeling for Critical Care -- Biomechanical Analysis of Abdominal Aortic Aneurysms -- The Cardiac Atlas Project: Towards a Map of the Heart -- In Vivo Myocardial Material Properties and Stress Distributions in Normal and Failing Human Hearts -- Modeling of Whole-Heart Electrophysiology and Mechanics: Toward Patient-Specific Simulations -- Personalized Computational Models of the Heart for Cardiac Resynchronization Therapy -- Patient-Specific Modeling of Hypoxic Response and Microvasculature Dynamics -- A Computational Framework for Patient-Specific Multi-Scale Cardiac Modeling.
Keywords: Medicine; Cardiology; Bioinformatics; Biomedical engineering; Biomedicine; Bioinformatics; Computational Biology/Bioinformatics.; Biomedical Engineering; Cardiology